Instrumental Assessment and Pharmacological Treatment of Migraine-Related Vertigo in Pediatric Age - Pasquale Viola; Alfonso Scarpa; Giuseppe Chiarella; Davide Pisani; Alessia Astorina; Filippo Ricciardiello; Pietro De Luca; Massimo Re; Federico Maria Gioacchini (Audiology Research, 2024)
Background: The most frequent form of vertigo in pediatric age is represented by vertigo linked to migraine, with a prevalence of 32.7%. This group of pathologies has received a redefinition of the diagnostic criteria to adapt them to the pediatric age with a new classification of the clinical pictures. We have several kinds of problems with these conditions that often have a significant impact on patients’ and parents’ quality of life: the diagnostic approach involves different tools for the different age groups contained in the pediatric range; the treatment of this type of vertigo is not consolidated due to the limited availability of trials carried out on pediatric patients. Focusing on this topic, the aim of this review was to provide an update on the more recent clinical advances in the diagnosis and treatment of Vestibular Migraine (VM) in children. Methods: We searched the PubMed, Embase, and Cochrane library databases for articles published in English from January 2015 to April 2023. The secondary search included articles from reference lists, identified by the primary search. Records were first screened by title/abstract, and then full-text articles were retrieved for eligibility evaluation. The searches combined a range of key terms (“Pediatric” AND “Childhood” AND “dizziness” OR “vertigo” AND “vestibular”). Results: Migraine-related vertigo, in its most recent definitions and classifications, is the most frequent group of balance pathologies in pediatric age. The results from the various experiences present in the literature suggest a clinical approach to be integrated with the use of instrumental tests selected according to the age of the patient and the reliability of the results. Conclusion: Knowing the timeline of the applicability of vestibular tests and the information that can be obtained from them is fundamental for diagnostic accuracy. Therapy is strongly conditioned by the limited availability of pediatric trials and by the wide range it includes, from very young children to adolescents.